MANAJEMEN KURIKULUM SEKOLAH ISLAM TERPADU DALAM RANGKA MENINGKATKAN KARAKTER SISWA SEKOLAH MENENGAH PERTAMA TERPADU MAâ€™ARIF MUNTILAN KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Â The purpose of this study is: (1) To determine the curriculum in junior management planning Integrated Ma'Arif Muntilan Magelang in order to improve students' character; (2) To determine the organization of the various components of the Integrated junior high school in Magelang Muntilan Ma'Arif order to properly implement the curriculum; (3) To determine the mobilization of the various components of the Integrated junior high school in Magelang Muntilan Ma'Arif; and (4) In order to determine surveillance Integrated curriculum in junior Maarif Muntilan Magelang.The study used a qualitative descriptive approach. Research at SMP ISAM Ma'Arif Gunungpring Muntilan Magelang. The study lasted for six months starting in May 2014 in the subject of this research is the principal, teachers, and administrators Administrative head of the school committee. Data collection methods in this study using interviews, observation and documentation. The analysis used is descriptive qualitative analysis.The final conclusion is that the management of the Integrated Islamic School curriculum in order to increase student kankarakter Secondary School Integrated Ma'Arif Gunungpring Muntilan Magelang District has worked well with implementing management planning curriculum, organizing the various components of the school, the mobilization of the various components of the school, as well as curriculum supervision optimal. It can be described as follows: 1) Planning Integrated management of the curriculum in junior Ma'Arif Muntilan Magelang in order to improve the character of the students is done every enters the new school year 2) The organization of the various components of the Integrated junior high school in Magelang Muntilan Ma'Arif order to properly implement the curriculum includes the school division of the school curriculum in order to enhance the student's character can be implemented;3) Mobilisation of the various components of the school includes students, teachers, staff, funds, facilities, curriculum and other resources of which include direct efforts of the school community to be willing to carry out the task; 4) The supervision over the management of the curriculum in order to improve students' character whom include monitoring the performance of school teachers in the implementation of the curriculum in improving the character of the student.